HUBUNGAN JOB INSECURITY TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN KONTRAK FOOD & BEVERAGE - Angelo, Gabriel; Sukardi, Angelita; Tendean, Christania Gloria; Arwi, Adelia Vannissa; Chandhika, Jessica (Psikologi Prima, 2023)
This study examines the relationship between Job insecurity and Organizational Citizenship Behavior in contract employees who work in the food & beverage sector. The measuring instrument used to conduct this research survey uses two measuring instruments that have been determined by the researchers, namely the Job Insecurity Questionnaire (JIQ) to measure Job Insecurity developed by (Chirumbolo et al., 2020) Meanwhile to measure Organizational Citizenship Behavior (OCB), researchers use a measuring instrument that developed by William and Anderson (1991) which has been adapted into Indonesian by (Graciaswaty et al., 2016) consisting of OCB-O and OCB-I. Data collection in this study was carried out using the non-probability sampling method or the selection of populations that were not random and the technique that the researchers used was the snowball sampling technique, namely taking the number of samples based on the interrelationships between people to one another which will be carried out continuously. Data analysis was carried out using a sample of 104 respondents, that were collected by distributing questionnaires online using Google forms and social media and offline by walking around and visiting respondents directly. The analysis test result was obtained with the help of the BM SPSS Statistics Version 25.0 software and using the Pearson correlation method, with a significance value of 0.33. It can be concluded that the Job Insecurity variable has no relationship with the Organizational Citizenship Behavior variable.